Deurbanization and the right to the deurbanizaed city - Sadri, Hossein; Zeybekoglu, Senem (ANDULI, Revista Andaluza de Ciencias Sociales, 2018)
Cities are historically created as a collaborative work of different generations and derive from the possibilities created bylocal and climatic conditions, social relations and culture. Today, urbanization may appear as a way of organizing everyday hierarchical, exclusive, discriminatory and exploitative life through industrialized mass production of temporary, privatized, homogenized, fragmented, and power-oriented spaces. This mind-set and application generates several social and ecological problems. This article discusses the right to the city concept, and links it to the deurbanization approach as a social and ecological answer to the problems associated with current urban development. The methodology is supported by a review of the literature and an analysis of examples of works created in the De-Urban Design Studio. Results indicate that the deurbanization approach envisions creating resilient, equitable, non-hierarchical cities composed of communities that replace consumption via harmony with nature, that replace individualism and competition viacollaboration and solidarity, and that replace hegemonic relations via an equitable distribution of power.